HABITAT DISTRIBUTION MODELS OF FLORES HAWK-EAGLE (Nisaetus floris) IN EAST NUSA TENGGARA - Syartinilia; Putra, Indeka Dharma Putra; Yeni Aryati Mulyani (Department of Forest Resources Conservation and Ecotourism - IPB University, 2023)
Flores hawk-eagle (Nisaetus floris) was a Critically Endangered endemic raptor species in Lesser Sunda Region, especially in East Nusa Tenggara. The lack of information and difficulties in reaching the Flores hawk-eagle's distribution area have caused difficulties in conservation efforts for this species. One of the efforts that could be made was by spatial modeling distribution of Flores hawk-eagle habitat in East Nusa Tenggara based on GIS. Using habitat distribution spatial modeling could predict the potential place where a species can live. Logistic regression was one of the methods applied in animal distribution spatial modeling, where this method was considered to have better accuracy. Through the analysis, it was found that the potential habitat for Flores hawk-eagle was 6390.48 km2 (22%), and the non-potential habitat was 22,459.59 km 2 (78%). The habitat factors that determine the distribution of the Flores hawk-eagle include slope, altitude, rice fields, plantation, forests, and shrubs. The availability of nesting trees and food for Flores Hawk-eagles may influence the distribution of existing habitats. The results of the distribution mapping of the Flores Hawk-eagle can be used as a reference in efforts to manage the habitat of the Flores hawk-eagle in East Nusa Tenggara. Key words: Endemic Raptor, Habitat Modelling, Logistic Regression, Nisaetus floris, Species Priority